2012
DOI: 10.1089/cap.2012.0003
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Attention-Deficit/Hyperactivity Disorder Medications in Children: An Intensive Pharmacosurveillance Monitoring Study

Abstract: Although our data provide reassurance of the safety of ATX and MPH, several unexpected or uncommon ADRs (hepatomegaly, suicidal ideation, weight gain, or drug interactions) were identified by our intensive pharmacosurveillance monitoring program. Our results show that an intensive pharmacosurveillance monitoring program that involves pharmacovigilance centers and clinicians can improve the collection of information on drug safety in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…We found four studies and two case reports that reported hepatic effects [18,30,[48][49][50][51][52]. The results are compatible with the rarity of reports of liver injury highlighted in the European SPC.…”
Section: Findings In the Predefined Literature Searchsupporting
confidence: 85%
See 4 more Smart Citations
“…We found four studies and two case reports that reported hepatic effects [18,30,[48][49][50][51][52]. The results are compatible with the rarity of reports of liver injury highlighted in the European SPC.…”
Section: Findings In the Predefined Literature Searchsupporting
confidence: 85%
“…Similarly, we have not discussed the extremely broad topic of overall tolerability. The manuscript was written using the seven predefined topics as headings, with all the papers selected during stages 2 and 3 [17][18][19][20][21] referred to under the appropriate heading(s) in Sect. 3.…”
Section: N=924mentioning
confidence: 99%
See 3 more Smart Citations